Evidence for the coexistence of spin-glass and ferrimagnetic phases in BaFe12O19 due to basal plane freezing. Issue 94 (12th November 2020) - Kumar, Keshav; Mishra, Shrawan Kumar; Baev, Ivan; Martins, Michael; Pandey, Dhananjai
Abstract : Spin-glass freezing in BaFe12 O19 without any substitutional disorder. Abstract : We present here the results of low-temperature magnetization and X-ray magnetic circular dichroism studies on the single crystals of BaFe12 O19 which reveal for the first time the emergence of a spin glass phase, in coexistence with a long–range ordered ferrimagnetic phase, due to the freezing of the basal plane spin component.